Oki stent application in different indications: Six cases. (13th July 2016) - Özgül, Mehmet Akif; Çetinkaya, Erdoğan; Çörtük, Mustafa; Tanrıverdi, Elif; Yıldırım, Binnaz Zeynep; Balci, Merih Kalamanoğlu; Issaka, Adamu; Özgül, Güler
Abstract: Introduction: We have used Oki stents for a number of different indications. After discovering that there are limited reports in the literature on these stents, we were motivated to share our experiences in Oki stenting. Objectives: While there is vast knowledge on double Y‐stents, the Oki stent is a relatively recent development in pulmonology. Here, we demonstrate that stenting of the right secondary carina using an Oki stent should be considered for obstructions in this region. Methods: We placed 13 mm × 10 mm × 9 mm Oki stents in six patients under general anesthesia via rigid bronchoscopy. Results: Three cases were post‐transplant patients with malacia, stenosis, and bronchopleural fistula. One case had an airway obstruction due to malignant disease, another case had a right aortic arc and aberrant left subclavian artery anomaly, and the final case had bronchopleural fistula. No serious complications were observed during stent placement. Conclusions: Oki stents can safely be used for many clinical conditions. Patients benefit greatly from stenting; however, two of our cases died due to infection, and one case died due to malignancy.